ENHANCEMENT OF FUEL BRICKET QUALITY BY IMPROVED FUEL TECHNOLOGY: Array - , О. С., О. В., В. І., О. С., Д. Ю. (Municipal economy of cities. Series: «Economy science», 2018)
It has been established that the existing technologies for the production of fuel briquettes are energy-intensive and use up to 60% of energy for drying and biomass. Made briquettes hygroscopic with low thermal capacity and strength. The classification of technological processes of biomass of the leading world companies is performed. The analysis of these three main technologies indicates that the calorific value, significant content of dust, small particles and hidden bacteria and mold in briquettes had a sign of poor quality, low mechanical strength and rapid erasure. This indicator is important during transportation, storage and supply of briquettes to the combustion boiler, as it can cause losses during loading and unloading operations, reducing their mass. In addition, when burned in small boilers, the small fraction clogs the feed augers, interferes with the supply of oxygen and thus can lead to a decrease in the efficiency of the boiler during combustion and also damage to precious equipment. The use of environmentally friendly binders makes it possible to improve the basic characteristics of heat capacity, strength, hygroscopicity and cost-effectiveness of manufacturing fuel briquettes. It is established that the use of microwave technology makes it possible to obtain a finished product of higher quality. When drying due to a decrease in the loss factor of the material is heated, the rate of temperature rise automatically decreases until the end of the process, while reducing the possibility of unacceptable overheating of the product. Technological processes using high-speed high-frequency heating are easy to mechanize and automate. The introduction of the high-frequency method of heating significantly improves sanitary and hygienic working conditions, but a certain disadvantage of the EMF briquetting technology is the urgent need to shield the EMF exclusively in the zone of interaction between the field and the substance and prevent its leakage beyond the maximum permissible levels. With rational selection of the frequency of oscillations and parameters of the chambers, where the conversion of microwave energy into heat takes place, it is possible to obtain a relatively uniform heat release throughout the body. Keywords: fuel briquettes, plant and wood waste, manufacturing technology.